Perancangan Prototipe Pengontrolan Cooling System Pada PLTS - Azwir Rezari; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Renewable energy is the solution of electricity generation to replace conventional electricity generation that used to use fossil fuels which will eventually run out. Solar energy or solar energy can be used to generate electricity through solar panel media, but the energy that is converted to produce electricity is energy from solar light instead of heat energy produced by the sun. Thermal energy from the sun is a problem for solar panels because it can reduce the efficient power produced by solar panels. Then the solution to overcome that is designed for watering the surface of the solar panel to increase the effectiveness of the power generated by controlling the panel using Arduino with LM35 sensors mounted on five points of the solar panel. With the results found the average increase in power on December 24 by 20% if the panel is given an automatic cooling system. Key word: Solar panels, panel cooling systems, Arduino.